Distention of the Immature Left Ventricle Triggers Development of Endocardial Fibroelastosis: An Animal Model of Endocardial Fibroelastosis Introducing Morphopathological Features of Evolving Fetal Hypoplastic Left Heart Syndrome. (3rd May 2015) - Shimada, Shogo; Robles, Christian; Illigens, Ben M. W.; Casar Berazaluce, Alejandra M.; del Nido, Pedro J.; Friehs, Ingeborg
Abstract : Background. Endocardial fibroelastosis (EFE), characterized by a diffuse endocardial thickening through collagen and elastin fibers, develops in the human fetal heart restricting growth of the left ventricle (LV). Recent advances in fetal imaging indicate that EFE development is directly associated with a distended, poorly contractile LV in evolving hypoplastic left heart syndrome (HLHS). In this study, we developed an animal model of EFE by introducing this human fetal LV morphopathology to an immature rat heart. Methods and Results. A neonatal donor heart, in which aortic regurgitation (AR) was created, was heterotopically transplanted into a recipient adult rat. AR successfully induced the LV morphology of evolving HLHS in the transplanted donor hearts, which resulted in the development of significant EFE covering the entire LV cavity within two weeks postoperatively. In contrast, posttransplants with a competent aortic valve displayed unloaded LVs with a trace of EFE. Conclusions. We could show that distention of the immature LV in combination with stagnant flow triggers EFE development in this animal model. This model would serve as a robust tool to develop therapeutic strategies to treat EFE while providing insight into its pathogenesis.